Characterization of Carbapenem Resistance in Bacteria Isolated from Clinical Samples in Lahore, Pakistan - Saleem, Mehwish; Latif, Ayesha; Ashraf, Asfa; Iqbal, Muhammad Naeem (International Journal of Nanotechnology and Allied Sciences, 2018)
The aim of the current study was to determine Carbapenem resistance in clinical isolates of bacteria. This study was carried out in Pathology Laboratory, Sir Ganga Ram Hospital, Lahore. To investigate the Carbapenem resistance, a total of 105 clinical samples such as blood, urine, pus, HVS, sputum and miscellaneous were collected from different patients. All clinical samples were subjected to conventional cultural and biochemical methods for microbial enumeration. Antibiotic susceptibility was analyzed using agar disk diffusion method. The results showed that among 105 samples collected 53 were males and 52 were females, illustrating that the infection ratio between genders was almost equal. Most of the infections were found in the age group 0 to 20 years and most of the prevalent bacterial isolates had also been reported in these samples. Prevalence of bacteria isolated was Escherichia coli (72.38%), followed by Staphylococcus aureus (20%), Klebsiella pneumoniae (4.76%), Pseudomonas aeruginosa (0.95%), Serratia (0.95%), and Proteus sp. (0.95%). Rate of resistance to Carbapenem was higher in females (8%) than in the males (6%). Among the bacterial isolates, the resistant strains were (n=22) 21% and remaining (n=79) 75% were sensitive towards Carbapenem. Bacteria which lie in intermediate group sensitive/resistant were (n=4) 4%. These results show that bacterial resistance is prevailing so rapidly.